ANALISIS MULTIVARIAT KEBUTUHAN AKADEMIK DAN MOTIVASI BELAJAR DALAM MENENTUKAN TINGKAT KETERGANTUNGAN MAHASISWA PADA LAPTOP - Iqbal, Muhammad; Maulana, Hildan; Aziz, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the influence of academic needs and learning motivation on students' level of laptop dependency, with intensity of use serving as a mediating variable. In the era of digital transformation, laptops have become primary instruments in higher education, massively influencing academic behavior. This research employs a quantitative approach using Covariance-Based Structural Equation Modeling (CB-SEM) via AMOS 24 software. The research population consists of 200 Industrial Engineering students at STT Wastukancana, selected using a purposive sampling technique. The results of the data analysis indicate that digital academic needs and intrinsic learning motivation have a positive and significant influence on the intensity of laptop use. Furthermore, intensity of use is proven to be a strong mediator ($p < 0.05$) in forming students' academic dependency. The structural model developed in this study is capable of explaining 70% of the variance in the academic dependency variable. The implications of this research emphasize the importance of digital literacy management and the provision of supporting infrastructure by educational institutions to mitigate the psychological risks of excessive technological dependency.